Design And Synthesis Of Chalcone Derivatives As Antidiabetic And Anticancer Agents - Narute, Ashok Sarjerao; Surwase, Kumar Pralhadrao (Journal of Neonatal Surgery, 2025)
Chalcones, an important class of natural and synthetic flavonoid precursors, have gained considerable attention in medicinal chemistry due to their wide spectrum of pharmacological activities, including antidiabetic and anticancer properties. Their simple chemical structure, ease of synthesis, and structural versatility make them attractive scaffolds for drug development. In this study, a series of novel chalcone derivatives were rationally designed and synthesized with the aim of exploring their dual therapeutic potential against diabetes and cancer.The synthesis of the target compounds was accomplished through the Claisen–Schmidt condensation reaction, involving various substituted aromatic aldehydes and ketones under optimized reaction conditions. This approach enabled the formation of structurally diverse chalcone analogs with different functional groups. The synthesized compounds were purified and characterized using standard analytical techniques such as Fourier Transform Infrared Spectroscopy (FT-IR), Nuclear Magnetic Resonance (¹H and ¹³C NMR), and mass spectrometry, confirming their chemical structures and purity.The biological evaluation of these derivatives demonstrated promising results. Several compounds showed significant inhibitory activity against key carbohydrate-hydrolyzing enzymes, namely α-amylase and α-glucosidase, which are crucial targets in the management of postprandial hyperglycemia in diabetes. These findings suggest their potential application as effective antidiabetic agents. In addition, the synthesized chalcone derivatives were screened for in vitro anticancer activity against selected human cancer cell lines. Notably, some compounds exhibited potent cytotoxic effects with good selectivity toward cancer cells, indicating their therapeutic relevance.Structure–activity relationship (SAR) analysis revealed that both electron-donating and electron-withdrawing substituents on the aromatic rings significantly influenced the biological activity of the compounds. Substituent position and type played a critical role in enhancing enzyme inhibition and anticancer efficacy. In conclusion, the present study highlights the potential of chalcone derivatives as multifunctional therapeutic agents with dual antidiabetic and anticancer activities. These findings provide a strong foundation for further investigations, including molecular docking studies, in vivo pharmacological evaluations, and toxicity assessments, to advance these compounds toward clinical development.